Biomechanical response comparison of Nigerian child Anthropometric Test Device (ATD) and Hybrid III dummy - Abdul Aziz, Nuraini; Rafukka, Ibrahim; Arumugam, Manohar (Segi University, 2024)
Anthropometric Test Devices (ATD) or crash dummies are used to simulate the response of human beings in crash tests of vehicles. There is concern about the difference in anthropometry of people from various locations of the world and current crash test dummies used in safety certification of vehicles. Three-year-old (3YO) Hybrid III dummy may not represent Nigeria children because they were produced using United States child anthropometry. The aim of this work is to investigate how the size of 3YO Nigeria child dummy affects crash injury outcomes in Finite Element (FE) crash analysis. FE dummy model that is scaled to Nigeria child anthropometry was used to simulate a sled test and the injury parameters such as head accelerations, chest acceleration and resultant upper neck moment and force were evaluated and compared with experimental results of with the view to ascertain how good can represent Nigerian child in crash test. The results show that is different from in head acceleration and chest acceleration by 29% and 6% respectively. Nigerian child resultant upper neck moment and force were 10% and 23% respectively lower than . Difference in the injury outcomes means that model cannot represent three-year-old Nigerian child in certification. Hence crash dummy of Nigerian child anthropometry is necessary in certifying vehicle safety performance for cars used in Nigeria.